Sorption parameters of Pb and Cu on natural clay soils from Selangor, Malaysia = Parameter penjerapan logam Pb dan Cu oleh tanah lempung dari Selangor, Malaysia - Wan Zuhairi W. Y,; Abdul Rahim S., (Universiti Kebangsaan Malaysia, 2007)
The sorption parameters of two heavy metals (i.e. Pb and Cu) in clay soils from Selangor were studied using batch equilibrium test. The test was conducted in two separate systems, i.e. single and mix solutions. The sorption isotherms data from this test were then used to calculate the sorption parameters, i.e. distribution coefficient (Kd) and maximum adsorption capacity (Am). Langmuir sorption equation was used to model the sorption data with the correlation coefficients(r2) higher than 0.6. The study has revealed that different soils have different sorption capacity for different heavy metals. The Kd values are proportional to the sorption capacity of the soils. The sorption of Pb and Cu in single solution is higher than in mix solution, due to the competition for sorption sites among heavy metals in mix solution. The Kd values for Pb in single solution ranging from 36.18 – 334.48 L/g and for Cu is 9.29-66.19 L/g. In mix solution, the Kd values for Pb and Cu are much smaller, ranging from 23.13-31.79 L/g and 3.95-18.53 L/g respectively. The Am values in single solution for both Pb and Cu are ranging from 0.48-1.09 mg/g dan 0.18-0.70 mg/g respectively. While in mix solution, the values of Am for Pb ranging from 0.20-1.11 mg/g and Cu within 0.18-0.60 mg/g.